Validasi SQ-FFQ dengan Estimated Food Record untuk Menilai Jumlah Asupan Buah Sayur dan Zat Gizi Mikro Mahasiswa - Adelia Listy Nursabrina (Lembaga Pengembangan Kinerja Dosen, 2025)
The percentage of the Indonesian population with insufficient fruit and vegetable intake remains relatively high, at 97.5% for individuals aged 15-19 years and 96.8% for those aged 20-24 years. The SQ-FFQ method can serve as an instrument to assess the intake of fruits, vegetables, and micronutrients to enhance the immune system of students. This study aims to explore the relationship between the daily fruit and vegetable intake of students in Surabaya using the SQ-FFQ method and the estimated food record as the main reference materials. The population of this study consists of students from various universities in Surabaya, class of 2021. The research indicates that the SQ-FFQ method can assess the average daily fruit and vegetable intake and micronutrient intake more accurately than the estimated food record method. The highest correlation value in the fruit and vegetable intake correlation test was found in the fruit group, while the highest correlation value for micronutrient intake was found in vitamin C intake. Based on the research findings, it was concluded that the SQ-FFQ method is a valid instrument for measuring the daily intake of fruits, vegetables, and micronutrients.